Institutional profile: Community for Open Antimicrobial Drug Discovery – crowdsourcing new antibiotics and antifungals. (24th March 2017) - Desselle, Mathilde R; Neale, Ruth; Hansford, Karl A; Zuegg, Johannes; Elliott, Alysha G; Cooper, Matthew A; Blaskovich, Mark AT
The Community for Open Antimicrobial Drug Discovery (CO-ADD) is a not-for-profit, collaborative approach to discovering new antibiotics. We access novel chemical diversity from academic synthetic chemists, who collectively possess millions of untested compounds with chemical diversity that lie outside commercial collections. We perform high-throughput antimicrobial screening of pure compounds derived from both synthetic and natural sources free of charge. The resulting data can be used by participants for publication, patenting and development purposes, and is fed back into the research community through an open-access database after a 2-year period during which information is kept confidential to the provider. CO-ADD is fundamentally asking two questions: can the community work together to address the global threat of antimicrobial resistance; and are there as yet undiscovered, novel antimicrobial compounds already present within our diverse global chemistry community?